PENGEMBANGAN MODEL PENDIDIKAN KARAKTER PEDULI SOSIAL MELALUI METODE BERMAIN PERAN DI TK TUNAS MEKAR INDONESIA BANDAR LAMPUNG - Agung, Putry; Asmira, Yulistyas Dwi (Jurnal Caksana : Pendidikan Anak Usia Dini, 2018)
ABSTRACTCharacter education is very necessary for the realization of national education goals. Over time, it is necessary to instill social caring character education since early age is a very important period of development in human life. Thus it is necessary to develop socially caring character education through learning role playing methods. The purpose of this study is to; Developing a character education model through the role playing method in TK Tunas Mekar Indonesia (TMI) Bandar Lampung. This study uses research and development methods with the following steps; (a) needs analysis, (b) planning includes compiling RPPM and RPPH (c) determining elements of character education; (d) collect learning material; (e) compile a model draft, (f) validation, (g) model revision, (h) model trial; and (i) product improvement. Data collection instruments used are; (1) questionnaire, (2) discussion, (3) interview. The data analysis technique that is carried out is quantitative descriptive analysis and qualitative descriptive analysis. This research produced a social caring character education model.Keywords: Character Education Model, Social Care, Role Playing.